Lipid biochemical and biophysical changes in rat spermatozoa during isolation and functional activation in vitro - Oresti, Gerardo Martin (2015)
n spermatozoa isolated from rat epididymis, lipids are differentially modified after in vitro induction of capacitation (Cap) and the acrosomal reaction (AR). This study uses Laurdan fluorescence generalized polarization values (GPv) to evaluate the effect of lipid changes occurring after isolation and functional activation on sperm membrane biophysical properties. In gametes isolated in the presence of a divalent cation chelator, no lipid changes occurred and the GPv were the lowest recorded, indicating maximal membrane lipid mobility. In sperm isolated as rapidly and gently as possible in the absence of chelator, part of the sphingomyelins (SM) were converted into ceramides (Cer), giving rise to higher GPv. In samples incubated as controls for Cap and AR, unchanged cholesterol and reduced glycerophospholipid levels were accompanied by the accumulation of free fatty acids (FFA), leading to even higher GPv. After completion of Cap, the GPv returned to lower levels as a result of the spermatozoa losing part of their cholesterol and FFA. Cap samples became relatively enriched in polyunsaturated fatty acids-containing plasmalogens because hydrolysis affected phosphatidyl rather than plasmenyl glycerophospholipid subclasses. The highest Cer:SM ratio and the highest GPv were found after completion of AR induced by A23187. The degree of SM → Cer conversion among the samples, including controls, correlated with the extent of AR. FFA and Cer augmented GPv when added to liposomes prepared from the membrane lipid of intact sperm. Our results underscore the importance of hydrolytic changes that affect sperm lipids, especially the decisive lipid SM and Cer pair, not only after inducing sperm functional changes such as Cap and AR, but also under control conditions.